A Application of the Problem Based Learning Model in Mathematics Content to Improve the Learning Outcomes of Class IV Elementary School Students - Marlina; Rahmah, Siti (Asian Journal of Applied Education (AJAE), 2023)
The purpose of this study was to improve student learning outcomes through the Problem Based Learning model for fourth grade students at SDN 1 Sungai Danau. This Classroom Action Research was carried out in two cycles using the Kemmis and Mc models. Taggart which consists of the stages of planning, implementation, observation and reflection. Data was collected through observation and tests. Data analysis uses qualitative and quantitative data. The results showed that the teacher's activity in learning activities was in the first cycle of meeting 1, namely 38, the second meeting, namely 41 and in Cycle II, meeting 1, namely 44, the second meeting, namely 53. The percentage of students' classical activity in Cycle I, meeting 1 reached 72%, meeting 2 reached 75% and in cycle II meeting 1 reached 78%, meeting 2 reached 91%. Completeness of student learning outcomes cycle I reached 75% and increased in cycle II reached 94%. The results of this study indicate that the application of the Problem Based Learning model to mathematics content can improve student learning outcomes in terms of the learning outcomes of fourth grade students at SDN 1 Sungai Danau.